Adherence to gluten free diet and problems faced by children with celiac disease and type 1 diabetes mellitus - Anjali Verma; Shilpi Rani; Surender Verma; Alok Khanna (Journal of Family Medicine and Primary Care)
Introduction Celiac disease (CD) in children can be associated with Type 1 Diabetes Mellitus (T1DM) as both share autoimmune etiology. Mainstay of treatment in celiac disease is total avoidance of gluten in diet whereas treatment in child with both the diseases will be Insulin therapy, exercise along with gluten free diet (GFD). There is dearth of literature regarding adherence to GFD and barriers for children with both T1DM and CD. Methods A questionnaire-based study was done at a tertiary care institute so as to compare the self-reported gluten adherence and the problems faced by children with dual diseases (TIDM and CD) and CD alone. Thirty children of age group 5-14 years each withType 1 DM and CD (T1DMCD group) and celiac disease (CD group) were selected consecutively. A questionnairewas filled by asking questions from either children (above 8 years) or parents (below 8 years) and the results were compiled, compared and further analysed. Results Baseline demographic parameters were comparable in both the groups. Gluten adherence was found to be worse in T1DMCD group as compared to CD group. Greater number of problems were experienced by children with both TIDM and CD as compared to children with CD alone (P < 0.05). Financial burden more so in T1DMCD group, unawareness about disease and benefits of GFD, less availability and social isolation were found to be the most significant barriers to diet adherence. Conclusion As these children face dual diseases, they should be made more aware regarding benefits of GFD. Such information is valuable to primary care physicians for better management and rehabilitation of children suffering from these chronic diseases.